Prevalence and Associated Factors of Insomnia among Elderly People of Nepalgunj Sub-Metropolitan City, Nepal - Ramesh Prasad Tharu; Ravi Singh Mahatra (AlQalam Journal of Medical and Applied Sciences, 2024)
Insomnia is a prevalent sleep-related complaint among older persons, regardless of whether it is reported as subjective symptoms or diagnosed as a sleep disorder by accepted diagnostic methods. The purpose of this study was to determine the prevalence of insomnia in the elderly, and the contributing factors to insomnia and their influence on the elderly people. A descriptive, cross-sectional research design was adopted, with a sample of 207 elderly people drawn from the Nepalgunj Sub-metropolitan City. Binary multiple logistic regression model was used to assess the factors contributing to insomnia in old aged people. The prevalence of insomnia found in the elderly was 52.3%. Among the different factors, females (OR: 3.21, 95% CI: 1.51 to 6.83), currently not working (OR: 4.25, 95% CI: 1.94 to 9.21), staying with spouse (OR: 3.26, 95% CI: 1.56 to 6.82), using sleeping pills (OR: 2.58, 95% CI:1.08 to 6.18), having chronic disease (OR: 2.67, 95% CI: 1.15 to 6.19), and physically inactive (OR: 7.93, 95% CI: 1.85 to 33.95) had significant association with insomnia. It can be inferred that more than half of the elderly people were suffering from insomnia. Females were 3.21 times more vulnerable to have insomnia as compared to males. الأرق هو شكوى شائعة تتعلق بالنوم بين كبار السن، بغض النظر عما إذا تم الإبلاغ عنه كأعراض ذاتية أو تم تشخيصه على أنه اضطراب في النوم عن طريق طرق التشخيص المقبولة. كان الغرض من هذه الدراسة هو تحديد مدى انتشار الأرق لدى كبار السن، والعوامل المساهمة في الأرق وتأثيرها على كبار السن. تم اعتماد تصميم بحثي وصفي مقطعي، مع عينة مكونة من 207 من كبار السن تم اختيارهم من مدينة نيبالغونج الفرعية. تم استخدام نموذج الانحدار اللوجستي الثنائي المتعدد لتقييم العوامل التي تساهم في الأرق لدى كبار السن. وبلغت نسبة انتشار الأرق لدى كبار السن 52.3%. من بين العوامل المختلفة، الإناث (نسبة الأرجحية: 3.21، فترة ثقة 95%: 1.51 إلى 6.83)، لا تعمل حاليًا (نسبة الأرجحية: 4.25، فترة ثقة 95%: 1.94 إلى 9.21)، تقيم مع الزوج (نسبة الأرجحية: 3.26، فترة ثقة 95%: 1.56) إلى 6.82)، باستخدام الحبوب المنومة (نسبة الأرجحية: 2.58، نطاق ثقة 95%: 1.08 إلى 6.18)، الإصابة بمرض مزمن (نسبة الأرجحية: 2.67، نطاق ثقة 95%: 1.15 إلى 6.19)، وغير نشط بدنيًا (نسبة الأرجحية: 7.93، نطاق ثقة 95%: 1.85 إلى 33.95) كان له ارتباط كبير بالأرق. ويمكن الاستدلال على أن أكثر من نصف كبار السن كانوا يعانون من الأرق. وكانت الإناث أكثر عرضة للإصابة بالأرق بنسبة 3.21 مرة مقارنة بالذكور